VCRIX - a volatility index for crypto-currencies - Alisa Kim; Simon Trimborn; Wolfgang Karl Härdle (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2019)
Public interest, explosive returns, and diversification opportunities gave stimulus to the adoption of traditional financial tools to crypto-currencies. While the CRIX index offered the first scientifically-backed proxy to the crypto- market (analogous to S&P 500), the introduction of Bitcoin futures by Cboe became the milestone in the creation of the derivatives market for crypto- currencies. Following the intuition of the "fear index" VIX for the American stock market, the VCRIX volatility index was created to capture the investor expectations about the crypto-currency ecosystem. VCRIX is built based on CRIX and offers a forecast for the mean annualized volatility of the next 30 days, re-estimated daily. The model was back-tested for its forecasting power, resulting in low MSE performance and further examined by the simulation of VIX (resulting in a correlation of 78% between the actual VIX and VIX estimated with the VCRIX model). VCRIX provides forecasting functionality and serves as a proxy for the investors' expectations in the absence of the de- veloped derivatives market. These features provide enhanced decision making capacities for market monitoring, trading strategies, and potentially option pricing.
Keywords: C51; C52; C53; G10; 330; index construction; volatility; crypto-currency; VCRIX